The Identification of Leading Agroindustries in South Kalimantan Province Indonesia - Luthfi Fatah; Tuti Heiriyani (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
Agroindustries have several positive roles in promoting regional economic development as well as improving income distribution. This study is primarily purposed to determine some leading agroindustries based on their financial, regional and distributional aspects. Research result shows that in ten districts of South Kalimantan Province Indonesia there are totally 17,881 units agroindustries consisting of 29 types. The majorities of agroindustries are large scale agroindustries. The leading agroindustries and appropriate districts as the central locations, where the agroindustries should be developed, are coconut oil and coconut cake industry in HSS, coffee powder industry in HST, brown sugar industry in BJR and salted fish industry in KTB. In addition, a further research is needed to study and formulate the strategy to improve agroindustries’ bargaining position in facing market. The research should also deal with the formulation of government’s supporting roles.